A comparison of soil carbon sequestration in hardwood and softwood monocultures (Case study: Dehmian forest management plan, Mazindaran) (مجله جنگل ایران, 2011)
Emission of carbon dioxide via human activities is known as the main cause of global warming. Appropriate forest management practices can have effective role to mitigate carbon emission as well as adsorb atmospheric carbon. The present research was carried out to investigate the effect of 35 years old Common ash (Fraxinus excelsior L.), Chestnut-leaved Oak (Quercus castaneifolia C.A.Mey), Norway spruce (Picea abies L. Krast) and Black pine (Pinus nigra Arn.) plantations on soil carbon sequestration in Dehmian plantation. Systematic soil sampling was done randomly. Totally 54 soil samples were taken from the top soil layers (0 – 10 and 10 – 20cm depths) in four plantations. Soil texture, pH, bulk density, electrical conductivity, organic carbon and total nitrogen were measured in the laboratory. Analysis of variance indicated that the amount of soil carbon sequestration of softwood plantations stands increased in comparison with hardwood ones. Results showed that the amount of soil carbon sequestration in Norway spruce stand (124.27 ton/ha) was significantly (P<0.05) higher than Black pine (94.67 ton/ha), Common ash (87.58 ton/ha) and oak (78.11 ton/ha). Results of stepwise regression showed that nitrogen percentage and C/N ratio were the most important factors affecting soil organic carbon content.